HUBUNGAN PENGETAHUAN, PERSEPSI, SOSIAL BUDAYA DENGAN PERAN AKTIF PRIA DALAM VASEKTOMI DI KECAMATAN PAGUYANGAN KABUPATEN BREBES TAHUN 2011-2012 (Unnes Journal of Public Health, 2015)
Participation rate of men in the use of contraceptives in Indonesia is still very low, at only 2.1 % men and they generally using a condom. Yet unsupported use of vasectomy as a contraceptive program is because of the social environment, culture, society and family are still considered male participation has not been or is not important, knowledge and awareness of men and their families in family planning still low. The purpose of this research was to know the correlation between knowledge, perseption and social culture in men’s active participation on vasectomy program. This research was observational with Cross Sectional study. This research was using simple random sampling technic. Based on the result of this research, there was significant correlation between perception and men's participation on vasectomy program (p value=0.047), there was significant correlation between social culture and men's participation on vasectomy program (p value=0.002), there was no correlation between knowledgeand men's participation on vasectomy program (p value=0.054). Vasectomy acceptors were suggested to become models by doing a persuasive approach through a familial conversation, so the other men have desire to contribute on vasectomy program.